Evaluation of inflammatory parameters in patients with hepatic hydatid disease - Zhijia Fan; Yao Hu; Li Wang; Haoqin Jiang; Dandan Li; Hui Zhao; Zhicheng Wang (Annals of Medicine, 2021)
AbstractBackground To the best of our knowledge, the association of inflammatory parameters with hepatic hydatid disease (HD) has not been investigated in a single study. We aimed to evaluate the potential value of inflammatory indices in this disorder.Methods The retrospective study including 114 patients was performed from January 2016 to November 2019. Clinical characteristics and laboratory data for all participants were collected and analysed. The levels of inflammatory parameters were compared in the patient and control group, the predictive value of these inflammatory parameters was assessed by the logistic regression analysis and receiver operating characteristic curve, and differences between pre- and post-surgical operations were compared by pair tests.Results Significantly higher levels of platelet distribution width (PDW), eosinophil percentage (EOS %), neutrophil to lymphocyte ratio (NLR), gamma-glutamyl transpeptidase to platelet ratio (GPR) and alkaline phosphatase to platelet ratio (APPR) and lower levels of platelet (PLT) and prognostic nutritional index (PNI) were observed in patients than in controls. Multivariate analyses showed that hydatid could induce the abnormal levels of these parameters, of which APPR and PNI had more obvious changes as compared to other parameters. The levels of PDW and APPR significantly decreased after surgical treatment.Conclusions Inflammatory parameters closely associated with the hepatic HD could be used in the evaluation of treatment as assistant indexes.KEY MESSAGEHydatid disease (HD) seriously endangers public health and economic development.Inflammatory parameters that are readily available and acceptable in routine clinical practice could be closely associated with HD.Inflammatory parameters could be used in the evaluation of disease development by combing with histological and radiological results in future studies.